An approach to empower social work students with entrepreneurial skills: Reflections on the social work curriculum in South Africa - Mkhize, Nkanyiso N.; Moganedi, Matshemo J.; Rapholo, Selelo F. (Social Work/Maatskaplike Werk, 2025)
Unemployment remains an unresolved social problem that has culminated in major socio-economic challenges across the globe, and South Africa is not an exception. Many young people in South Africa, including social work graduates are unemployed, contributing to the high rate of poverty. South Africa have endured a wave of unemployed social work graduates for the past decade, yet the increase in social problems justifies the need for more practitioners. This paper acknowledges the gap between the current social work curriculum and the need for innovation. The empowerment theory is used as a lens to explore innovative strategies to integrate entrepreneurial skills into the social work curriculum to curb the scourge of unemployment amongst social work graduates. Whilst the unemployment of social work graduates is alarming, there is limited research that rigorously explores this area from a social work perspective. There is a need for the social work curriculum to empower social work students with entrepreneurial knowledge and skills to mitigate the impact of unemployment faced by social work graduates. A desktop systematic review was used as a research methodology to conduct the literature review by purposefully focusing on social work education, social work unemployment and entrepreneurship.